Engineering Applications of Computational Fluid Dynamics - Shaari, Ku Zilati Ku.; Awang, Mokhtar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume presents the results of Computational Fluid Dynamics (CFD) analysis that can be used for conceptual studies of product design, detail product development, process troubleshooting. It demonstrates the benefit of CFD modeling as a cost saving, timely, safe and easy to scale-up methodology.
Reaction Modeling for Prediction of Hydrogen Production during Biomass Gasification -- Large Eddy Simulation (LES) for Steady-state Turbulent Flow Prediction -- Numerical Simulations of Lid-Driven Cavity Flows using Multi-relaxation Time Lattice Boltzmann Method -- Localization of Rotating Sound Sources using Time Domain Beam forming Code -- Effects of the Surrounding Fluid on the Dynamic Characteristics of Circular Plates -- CFD Modelling of the Coanda Based Thrust Vectoring Nozzle -- Numerical Investigation of the Flow over Delta Wing and Reverse Delta Wing -- Numerical Modeling and Research of 3D Turbine Stage -- Unsteady Interaction Effects between an Airship and Its Air-Jet Propulsion System -- Numerical Investigation on the Nanofluid Flow and Heat Transfer in a Wavy Channel.
Keywords: Fluid mechanics; Fluids; Physics; Engineering Fluid Dynamics; Fluid- and Aerodynamics; Numerical and Computational Physics, Simulation